Development of an ELISPOT assay for numerating IFN-γ-secreting T cells in chicken using novel monoclonal antibodies - Zhou Zhou; Ji Wu; Huining Zhang; Xinjie Yuan; Ye Meng; Lina Chen; Yi Yang; Xiaoli Hao; Shaobin Shang (Poultry Science, 2025)
Cellular immune responses play critical roles in the control of pathogenic infection. The measurement of antigen-specific IFN-γ-secreting T cells via an enzyme-linked immunospot assay (ELISPOT) is a valuable method for the evaluation of cellular immune responses. However, in chicken, few of monoclonal antibodies (mAbs) against chicken IFN-γ (chIFN-γ) are suitable for this application. In this study, three anti-chIFN-γ mAbs (2B10, 3F10, 5A7) were generated by immunization with pcDNA-chIFN-γ plasmid and recombinant Hela cell line stably expressing chIFN-γ (Hela-chIFN-γ). Indirect immunofluorescence assay showed that these mAbs specifically recognized eukaryotically-expressed chIFN-γ in DF-1 cells and natural chIFN-γ secreted by mitogen-activated chicken splenocytes. Furthermore, using 3F10 as a capture antibody and biotinylated 5A7 as a detection antibody, an ELISPOT assay was established for numerating IFN-γ-secreting T cells of chicken. This chIFN-γ ELISPOT assay had higher reactivity than a commercially available kit and showed no cross-reactivity with activated lymphocytes from geese and ducks. This assay was further applied to detect the frequency of MDV antigen-specific IFN-γ-secreting T cells in the spleen of CVI988-immunized chickens. Collectively, we developed and validated an ELISPOT assay for detecting IFN-γ-secreting T cells in chickens using novel anti-chIFN-γ mAbs. Our study provides an important immunological tool for in-depth analysis of cellular immune response in chicken after infection or vaccination.